Profil penggunaan antibiotik pada pasien pneumonia di komunitas: tinjauan pustaka - Nanda Faradita; Rika Yulia; Fauna Herawati (Intisari Sains Medis, 2022)
Background: Community pneumonia referred to as community acquired pneumonia is pneumonia that is often found in the community and the leading cause of death for infectious diseases. This pneumonia requires therapy with antibiotics. One of the main problems in using antibiotics is the occurrence of antibiotic resistance. This study aims to determine the profile of antibiotic use in patients with community acquired pneumonia, which is commonly referred as acquired pneumonia in the community. Methods: This study is a literature review that uses articles with a randomized controlled trial design and articles in Indonesian or English and has a publication year, namely the last 10 years. The keywords used were "Treatment" AND "Community acquaired pneumonia" AND "Antibiotic or Antimicrobial" AND "Mortality OR Clinical response OR Severity". Results: The quality of journals in this study was assessed by means of a critical appraisal skills program checklist and journal reputation. The results obtained were 9 articles that met the inclusion and exclusion criteria. The antibiotic that is often used in outpatient community acquired pneumonia without comorbidities is nemonoxacin 500 mg and in non-severe hospitalized patients the commonly used antibiotic is beta-lactam monotherapy. Conclusion: The conclusion in this study is that the antibiotic that is often used in outpatient CAP patients is Nemonoxacin 500 mg while inpatient CAP is beta-lactam monotherapy so that in both groups the use of antibiotics is not in accordance with the 2019 ATS guidelines therefore requires monitoring the use of antibiotics in patients with community acquired pneumonia.   Latar belakang: Pneumonia komunitas atau biasanya disebut dengan community acquired pneumonia yaitu pneumonia yang sering didapatkan di masyarakat dan merupakan penyebab kematian penyakit menular tertinggi. Pneumonia ini membutuhkan terapi dengan menggunakan antibiotik. Salah satu masalah utama dalam penggunaan antibiotik adalah terjadinya resistensi antibiotik. Penelitian ini bertujuan untuk mengetahui profil penggunaan antibiotik pada pasien community acquired pneumonia atau biasanya disebut dengan pneumonia yang didapatkan di komunitas. Metode : Penelitian ini merupakan kajian literatur yang menggunakan artikel dengan desain randomized controlled trial dan artikel yang menggunakan bahasa Indonesia atau bahasa inggris dan memiliki tahun publikasi yaitu 10 tahun terakhir. Kata kunci yang digunakan adalah "Treatment" AND "Community acquaired pneumonia" AND “Antibiotic or Antimicrobial” AND “Mortality or Clinical response or Severity”. Hasil : Kualitas jurnal pada penelitian ini dinilai dengan checklist critical appraisal skill program dan  reputasi jurnal. Hasil yang didapatkan adalah 9 artikel yang memenuhi kriteria inklusi dan ekslusi. Antibiotik yang sering digunakan pada pasien community acquired pneumonia rawat jalan tanpa komorbiditas adalah nemonoxacin 500 mg dan pada pasien rawat inap non severe antibiotik yang sering digunakan adalah monoterapi beta-laktam Kesimpulan : pada penelitian ini adalah Antibiotik yang sering digunakan pada pasien CAP rawat jalan adalah Nemonoxacin 500 mg sedangkan pada  CAP  rawat inap  adalah monoterapi beta-laktam sehingga pada kedua kelompok tersebut penggunaan antibiotik tidak sesuai dengan guideline ATS tahun 2019 sehingga masih membutuhkan pengawan penggunaan antibiotik pada pasien community acquired pneumonia.